2017
DOI: 10.1002/lno.10564
|View full text |Cite
|
Sign up to set email alerts
|

Trace metal composition of size‐fractionated plankton in the Western Philippine Sea: The impact of anthropogenic aerosol deposition

Abstract: The surface water of the Western Philippine Sea (WPS) receives a significant amount of anthropogenic aerosols from East Asia, serving as an ideal location to investigate the impact of anthropogenic aerosol deposition on trace metal composition and cycling in the Northwestern Pacific Ocean (NWPO). As part of the Taiwan GEOTRACES process study, we have collected size-fractionated plankton from surface water to investigate their metal composition in the open ocean. Elemental ratios in plankton, P-and Al-normalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 46 publications
7
30
0
Order By: Relevance
“…Then all the membranes were immediately sealed in 7‐ml Teflon vials and brought back to land‐based laboratory for further treatment and analysis. The sampling procedures and the description of the filtration device are described in details in our previous studies (Ho et al, ; Liao et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Then all the membranes were immediately sealed in 7‐ml Teflon vials and brought back to land‐based laboratory for further treatment and analysis. The sampling procedures and the description of the filtration device are described in details in our previous studies (Ho et al, ; Liao et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…All elemental concentrations reported were analyzed by a sector field high‐resolution ICPMS (Thermo Fisher Scientific, Element XR), which was executed with a SC‐Fast autosampler (Elemental Scientific) and an Apex HF‐Spiro membrane desolvation device (Elemental Scientific) to reduce oxide interferences. The details for the precision, accuracy, and detection limits of the method were described previously (Ho et al, ; Liao et al, ). The overall procedure blanks, detection limits, and the recovery of the reference material (BCR‐414) obtained in this study were consistent with results reported in Liao et al ().…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations